(untitled) (University Arena, 2025)
Research question aims to optimize functional training of female students in university physical education by practicing aerobic gymnastics. The experimental program was developed and then investigated functional parameters were female students were included in the experiment. Dynamic indices of control and experimental group was statistically interpreted one year after application of the experimental program. It was assumed that the use of specific aerobic gymnastics in physical education lessons with students in higher education, will contribute substantially to optimize their level of functional training.